1985
DOI: 10.1111/j.1471-4159.1985.tb07110.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cortico‐Striate Pathway Lesion on the Activities of Enzymes Involved in Synthesis and Metabolism of Amino Acid Neurotransmitters in the Striatum

Abstract: The activities of several enzymes involved in the metabolism of aspartate and glutamate were measured in striatal (nucleus caudatus and putamen) homogenates 2-3, 6-7, and 35-40 days following frontoparietal and frontal cortical ablation. The activity of glutamine synthetase (GS) was substantially increased (46-48%) on the operated side 6-7 days following the lesion whereas smaller changes were observed at 2-3 and 35-40 days after lesion. In contrast, decreased levels of glutaminase and malate dehydrogenase (MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 35 publications
3
28
0
Order By: Relevance
“…Lesioning the ipsilateral substantia nigra by 6-hydroxydopamine results in increased striatal levels of mRNAs encoding glumatic acid decarboxylase and proenkephalin; the changes in mRNA levels peaked on day 25 and lasted for a few months (Vernier et al, 1988). The time-courses of these two studies may be different from the present work because microsurgical dissection (Sandberg et al, 1985) or chemical lesion (Vernier et al, 1988) was used rather than focal ischemia, and because the brain region and the neurotransmitter systems studied are different. Our results do not differentiate whether the increase in neuropeptide levels in the amygdala is due to increased synthesis, increased axonal transport, or reduced release.…”
Section: Changes Of Npy 1-enk Dyn and Ntmentioning
confidence: 48%
See 1 more Smart Citation
“…Lesioning the ipsilateral substantia nigra by 6-hydroxydopamine results in increased striatal levels of mRNAs encoding glumatic acid decarboxylase and proenkephalin; the changes in mRNA levels peaked on day 25 and lasted for a few months (Vernier et al, 1988). The time-courses of these two studies may be different from the present work because microsurgical dissection (Sandberg et al, 1985) or chemical lesion (Vernier et al, 1988) was used rather than focal ischemia, and because the brain region and the neurotransmitter systems studied are different. Our results do not differentiate whether the increase in neuropeptide levels in the amygdala is due to increased synthesis, increased axonal transport, or reduced release.…”
Section: Changes Of Npy 1-enk Dyn and Ntmentioning
confidence: 48%
“…Previous stildies have demonstrated compensatory changes in the levels of the enzymes or mRNA that are involved in the synthesis and metabolism of neurotransmitters within deafferented areas (Sandberg et al, 1985;Vernier et al, 1988). Sandberg and colleagues (1985) reported changes in levels of striatal enzymes for the synthesis and degradation of glutamate and glutamine following fronto-parietal decortication.…”
Section: Changes Of Npy 1-enk Dyn and Ntmentioning
confidence: 97%
“…Interestingly, this enzyme can be detected in the cerebrospinal fluid of patients in advanced stages of Alzheimer disease (32). In some in vivo injury paradigms, neuronal degeneration is accompanied by an increase in astrocyte GS (33)(34)(35)(36). This increase has been attributed to reactive astrocytosis that occurs in response to neural insults and might be part of an endogenous mechanism for neuroprotection.…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that GS activity can be used as a biochemical marker of reactive gliosis (Sandberg et al, 1985). We have previously reported a transient increase of GS activity in a model of gliosis secondary to a neurotoxic lesion in the rat hippocampus (Condorelli et al, 1988).…”
Section: Introductionmentioning
confidence: 98%